Butorphanol Suppresses the Proliferation and Migration of Osteosarcoma by Promoting the Expression of piRNA hsa_piR_006613 - Cui, Pengfei; Xin, Deqian; Li, Fu; Deng, Lin; Gao, Yujie (Frontiers in Oncology, 2022)
Butorphanol, a partial agonist of opioid receptor κ 1 receptor, can and is widely used as an analgesic drug to relieve moderate and severe pain in clinic. Osteosarcoma is one of the most common malignant bone tumor in adolescents under the age of 20. To our knowledge no study has investigated the effect of butorphanol on the proliferation of osteosarcoma cells. In this study, The proliferation of osteosarcoma cells was measured by CCK-8 and colony formation assays, and the migration of osteosarcoma cells were detected by scratch and transwell assays. The expression of piRNA was detected by RNA sequencing and real-time PCR. PiRNA mimics or inhibitors have been used to upregulate or inhibit piRNA expression in osteosarcoma cells, respectively. We found that butorphanol, at the concentration of 10ug/ml or higher, could significantly inhibit the proliferation and migration of osteosarcoma cells. Our resuslts indicated that butorphanol promoted the expression of piRNA hsa_piR_006613 and overexpression of piRNA hsa_piR_006613 inhibited the proliferation and migration of osteosarcoma cells. our study also showed that inhibition of the expression of piRNA hsa_piR_006613 could promote the proliferation and migration of osteosarcoma cells. Butorphanol played the regulatory role on osteosarcoma cells in dependent of piRNA hsa_piR_006613. Butorphanol was found to inhibit the proliferation and migration of osteosarcoma cells by promoting piRNA hsa_piR_006613 expression. Bioinformatics analysis showed that hsa_piR_006613 downregulated FN1 protein expression by binding with 3’-UTR of FN1 mRNA. In all, the present research indicated that butorphanol suppresses the proliferation of osteosarcoma by promoting the expression of piRNA hsa_piR_006613, which downregulated the expression of FN1. Has_piR_006613 may become a new therapeutic target for osteosarcoma.